2007
DOI: 10.1021/jp066569p
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Photophysical, and Nonlinear Absorption Properties oftrans-Di-arylalkynyl Platinum(II) Complexes with Phenyl and Thiophenyl Groups

Abstract: Optical power limiting and luminescence properties of two Pt(II) complexes with thiophenyl and phenyl groups in the ligands, trans-Pt(P(n-Bu)3)2(C[triple bond]C-Ar)2, where Ar = -C4H2S-C[triple bond]C-p-C6H4-n-C5H11 (1) and -p-C6H4-C[triple bond]C-C4H3S (2), have been investigated. The fluorescence lifetimes were found to be on the sub-nanosecond time scale, and the quantum yields were low, in accord with fast intersystem crossing from the excited singlet to triplet manifold. The phosphorescence lifetimes of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 62 publications
9
62
0
Order By: Relevance
“…By the use of time-correlated single photon counting (TC-SPC), lifetimes in the range ∼50 ps to 1 μs can be determined (i.e., fluorescence). 69 Longer lifetimes due to phosphorescence can usually be measured directly with a fast photodiode or other schemes utilizing the photon counting PMT detector, such as multichannel scaling (MSC). 70 If an fs-laser is used for excitation, one can readily measure the two-photon absorption with the same data collection system (see below).…”
Section: General Appearance Of Linear Absorption and Emission Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…By the use of time-correlated single photon counting (TC-SPC), lifetimes in the range ∼50 ps to 1 μs can be determined (i.e., fluorescence). 69 Longer lifetimes due to phosphorescence can usually be measured directly with a fast photodiode or other schemes utilizing the photon counting PMT detector, such as multichannel scaling (MSC). 70 If an fs-laser is used for excitation, one can readily measure the two-photon absorption with the same data collection system (see below).…”
Section: General Appearance Of Linear Absorption and Emission Processesmentioning
confidence: 99%
“…The pulse-picker is necessary to reduce the pulse repetition frequency (PRF) of the laser if longer lifetimes are to be investigated. 68,69 By scanning the monochromators, the spectral properties for a given excitation wavelength and pulse configuration can be systematically studied. A representative fluorescence lifetime decay of C110 and phosphorescence decay of Pt-OEP are shown in Fig.…”
Section: General Appearance Of Linear Absorption and Emission Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,10,11] Complex 1a has been extensively studied in solution for its nonlinear absorption properties, [5,[10][11][12] and we have recently prepared several related molecules with repeating arylethynyl groups in trans configuration for comparisons with 1a. [13][14][15][16][17] The solution OPL studies of platinum polymeric structures have also been reported recently. [18][19][20] The solutions of the compounds (usually in tetrahydrofuran) show good OPL properties and are fairly transparent in the visible region.…”
Section: Introductionmentioning
confidence: 95%
“…The platinum acetylides are characterized by fast inter system crossing times, high excited state absorption, good two-photon absorption and long triplet lifetimes [9,47]. The singlet absorption peak is often in the UV/deep blue range while the triplet absorption cover a wide wavelength range [13,[46][47][48][49][50][51]. The low ground state absorption of platinum acetylenes in the visible make them excellent reverse saturable absorbers (section 1.3.3) [47].…”
Section: Introductionmentioning
confidence: 99%